Analisis Resepsi pada Konten Review Food Vlogger TikTok @Codebluuuu Studi Kasus Warung Nyak Kopsah di Cipondoh Tangerang - Nurkinan; Rosmala, Nina; Adityasning Arindawati, Weni (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to understand the meaning given by TikTok @Codebluuuu followers to the video review and how they are positioned in interpreting it. This research uses an interpretive paradigm, this research uses a descriptive qualitative approach with the reception method applied, referring to Stuart Hall's classification: dominant-hegemonic, negotiation, and opposition. Informants were selected using purposive sampling method based on criteria that are in accordance with the research objectives. The results showed that informants divided the meaning of video reviews into two sides: positive and negative. The positive side sees criticism as learning and encouragement of improvement for business actors, while the negative side views it as adversely affecting Nyak Kopsah's business reputation. The majority of informants are in the Negotiate position, accepting the dominant ideology but resisting its full implementation. They recognized the importance of honest criticism of food quality and prices for consumer information, but adjusted their views based on personal experience and social environment. In addition, they emphasized that the way in which criticism is delivered by Codebluu must be considered so as not to cause excessive negative effects.